226k views
4 votes
Expand binomial using binomial expansion (x-y)^3

User Pieterjan
by
6.2k points

1 Answer

4 votes

The expression is,


(x-y)^3

Expanding the expression we get,


(x-y)^3=(x-y)(x-y)^2\ldots.(1)

We have,


(x-y)^2=x^2-2xy+y^2\ldots..(2)

Substituting equation 2 in equation 1, we get,


\begin{gathered} (x-y)^3=(x-y)(x^2-2xy+y^2) \\ \text{ =}x(x^2-2xy+y^2)-y(x^2-2xy+y^2) \\ \text{ =}x^3-2x^2y+xy^2-yx^2+2xy^2-y^3 \\ \text{ =x}^3-y^3+3xy^2-3x^2y \end{gathered}

User Bjoernwibben
by
5.5k points